Anti-staphylococcal activities of lysostaphin and LytM catalytic domain - Sabala, Izabela (BioMed Central, 2012)
BACKGROUND: Lysostaphin and the catalytic domain of LytM cleave pentaglycine crossbridges of Staphylococcus aureus peptidoglycan. The bacteriocin lysostaphin is secreted by Staphylococcus simulans biovar staphylolyticus and directed against the cell walls of competing S. aureus. LytM is produced by S. aureus as a latent autolysin and can be activated in vitro by the removal of an N-terminal domain and occluding region. RESULTS: We compared the efficacies of the lysostaphin and LytM catalytic domains using a newly developed model of chronic S. aureus infected eczema. Lysostaphin was effective, like in other models. In contrast, LytM was not significantly better than control. The different treatment outcomes could be correlated with in vitro properties of the proteins, including proteolytic stability, affinity to cell wall components other than peptidoglycan, and sensitivity to the ionic milieu. CONCLUSIONS: Although lysostaphin and LytM cleave the same peptide bond in the peptidoglycan, the two enzymes have very different environmental requirements what is reflected in their contrasting performance in mouse eczema model.